OC-019 Iron Deficiency Anaemia and Hepcidin Levels in H. Pylori Infected Patients. (17th August 2016) - White, JR; Al-Hassi, HO; Reddiar, D; Mangalika, M; Cvijan, D; Falcone, Y; Worton, N; Lingaya, M; Figgins, A; Kaye, P; Ragunath, K; Atherton, JC; et al.
Abstract : Introduction: IDA affects up to 5% of the adult population in the developing world. There is an association between H. pylori (Hp) infection and incidence of unexplained IDA, but the mechanisms remain unclear. In children it has been suggested that Hp disturbs the iron regulatory mechanism via hepicidin. This peptide hormone induces internalisation and degradation of the iron transporter protein ferroportin thus limiting iron absorption and release. Hepcidin expression is induced by inflammation, but how this relates to Hp and IDA has not been fully elucidated, particularly in adults. This pilot study aimed to characterise local and systemic iron transporter expression in IDA patients with and without Hp infection, in comparison to Hp negative dyspepsia controls. Methods: Patients undergoing routine endoscopy for IDA (HpIDA and IDA groups, n = 18 and 40 respectively) or without IDA (control group, n = 18) donated blood and biopsy samples with informed consent and ethical approval. Hp status was assessed by three biopsy based tests and by serology. Duodenal and gastric biopsies were evaluated by immunohistochemistry for ferroportin and hepcidin, in addition to H&E staining for inflammation and atrophy grading. All scoring was carried out by experienced blinded histopathologists. A commercial ELISA assay was used to quantify serum Hepcidin-25. Results: As expected, anaemia parameters were significantly lower in the HpIDA and IDA groups compared to the controls (P < 0.0001). Surprisingly, serum hepcidin concentrations were significantly reduced in the HpIDA and IDA groups compared to the controls (9 fold, P = 0.009 and 5 fold, P < 0.0001 respectively). Hp infection was associated with gastric expression of hepcidin, particularly in the corpus when compared to controls. This corresponded with the cytoplasmic relocalisation of ferroportin (n = 12; 67%) in the duodenal enterocytes of patients with HpIDA compared to controls, where the ferroportin was actively expressed. Hepcidin was also found to be expressed in the duodenum of both controls and HpIDA. Significant atrophy was observed in both IDA groups. Conclusion: IDA was associated with significantly lower levels of serum hepcidin in contrast to previous studies. Local or systemic factors such as inflammatory mediators could be driving this response as more severe atrophy was observed in both IDA groups. We now aim to perform quantitative analysis of hepcidin in the gastric specimens using RT-qPCR to further evaluate whether local Hp transcriptionally upregulated hepcidin expression might cause these effects on iron transport. Disclosure of Interest: None Declared